Perancangan Sistem Monitoring Detak Jantung Bagi Penderita Kardiovaskular Berbasis Internet of Things - Muhamad Bahrul Ulum; Masmur Tarigan (Jurnal Komputasi, 2020)
The form of an archipelago and densely populated country of Indonesia has its own constraints in efforts to deal with health, especially health for patients with cardiovascular disease. This disease is one of the highest causes of death in Indonesia. Based on data from the Ministry of Health, cardiovascular disease since 2007 is the highest cause of death in Indonesia with more than 220,000 deaths each year. While the number of cases exceeds tuberculosis, which has a death toll of 127,000. The number is increasing every year due to changes in lifestyle of Indonesian people who like to eat high-fat foods and lifestyle factors that affect the risk of cardiovascular disease, including lack of physical activity, smoking, high-fat diets, and alcohol consumption habits. This study aims to monitor the heart rate of cardiovascular sufferers with the internet of things (IoT) approach. Every patient with cardiovascular disease can be monitored using a sensor connected to a PC to record any changes that occur. The research method consists of several stages, namely: Prepare, Plan, Design, Implement, Operate and Optimize (PPDIOO). The results obtained in the form of a prototype heart rate monitoring system for patients with cardiovascular. The patient's health can be monitored at any time by the hospital doctor without the patient having to come regularly to the hospital.